112k views
14 votes
I need the answer to this question

I need the answer to this question-example-1

1 Answer

7 votes

9514 1404 393

Answer:

g(x) = (5x +26)/(x+5)

Explanation:

To translate the function right h units and up k units, the transformation is ...

f(x -h) +k

You want h=-4 (4 units left) and k=-1 (1 unit down). So, the translated function is ...


f(x+4)-1=(6(x+4)+7)/((x+4)+1)-1\\\\=(6x+31)/(x+5)-1=(6x+31-(x+5))/(x+5)\\\\=(5x+26)/(x+5)

The translated function is ...

g(x) = (5x +26)/(x+5)

__

The original function is in red with asymptotes shown in orange. The translated function is in purple with the asymptotes shown in blue. You can see that the function has been moved 4 left and 1 down.

I need the answer to this question-example-1
User Robjtede
by
4.4k points